Impact and mechanism of rural labor migration on forest management income: Evidence from the Jiangxi Province, China - Ning, Caiwang; Xie, Fangting; Xiao, Hui; Rao, Pan; Zhu, Shubin (Frontiers in Environmental Science, 2022)
This article explores how rural labor migration affects the forest management income. Based on consecutive annual surveys of 397 forest households in the Jiangxi Province from 2011 to 2018, the panel-Tobit and IV-Tobit and mediation models are conducted. The studies showed that the migration effect of labor migration inhibits forest management income, and the remittance effect of labor migration has a promoting effect, but the total effect of labor migration inhibited household forest management income. A heterogeneity analysis showed that, the labor migration effect in hilly and mountainous areas has a significant inhibitory effect on forest management income, while the promoting effect of the remittance effect of labor migration on forest management income is only significant in plain areas. At the same time, compared with the elderly group, the migration effect of labor migration of the youth group has a greater inhibitory effect on household forest management income, while the impact of the remittance effect of labor migration is only significant in the elderly group. A test of action mechanism showed that, cash investment plays a partial mediating role on the impact of labor migration effect on forest management income, but it has a suppressing role in the impact of the remittance effect. Labor input plays a partial mediating role on both the labor migration effect and the labor remittance effect on forest management income. Our analysis provides an important basis for policymakers to formulate pertinent policies to support forest management in collective forest regions.